Analysis of national data shows mixed evidence of hardening among Australian smokers - Coral Gartner; Michelle Scollo; Louise Marquart; Rebecca Mathews; Wayne Hall (Elsevier, 2012)
Abstract Objective : According to the 'hardening hypothesis', the proportion of smokers that are 'low‐probability quitters' will increase as societal disapproval of smoking increases. This paper examines whether there has been increased hardening in Australian smokers over the past decade as reflected in an increased prevalence of psychological distress and social disadvantage among current smokers. Methods: The relationship between psychological distress, living in a disadvantaged area and level of education was determined using logistic regression at two time points 7 to 10 years apart in three cross‐sectional household survey series: National Drug Strategy Household Survey (NDSHS), National Health Survey (NHS) and National Survey of Mental Health and Well‐being (NSMHW). Results: The relationships between smoking and living in the most disadvantaged areas and having completed less than 12 years of schooling strengthened between 2001 and 2010 in the NDSHS, but there were no significant changes between survey years in the NHS and NSMHW. There was no significant change in the relationship between smoking and psychological distress between survey years in any of the survey series. Conclusion: Social disadvantage may be increasing among current smokers, but the results were inconsistent between survey series, presenting weak evidence that the population of Australian smokers hardened as smoking prevalence declined by approximately 4% over the last decade. Implications: A greater focus on intensive individual‐level tobacco cessation interventions does not appear warranted at this time.